A Puncture‐Resistant and Self‐Healing Conductive Gel for Multifunctional Electronic Skin - Hou, Ke‐Xin; Zhao, Shu‐Peng; Wang, Da‐Peng; Zhao, Pei‐Chen; Li, Cheng‐Hui; Zuo, Jing‐Lin (Advanced functional materials, 2021)
Flexible electronic skins (e‐skins) play a very important role in the development of human–machine interaction and wearable devices. To fully mimic the functions of human skin, e‐skins should be able to perceive multiple external stimuli (such as temperature, touch, and friction) and be resistant to injury. However, both objectives are highly challenging. The fabrication of multifunctional e‐skins is difficult because of the complex lamination scheme and the integration of different sensors. The design of skin‐like materials is hindered by the trade‐off problem between flexibility, toughness, and self‐healing ability. Herein, flexible sodium methallyl sulfonate functionalized poly(thioctic acid) polymer chains are combined with rigid conductive polyaniline rods through ionic bonds to obtain a solvent‐free polymer conductive gel. The conductive gel has a modulus similar to that of skin, and shows good flexibility, puncture‐resistance, notch‐insensitivity, and fast self‐healing ability. Moreover, this conductive gel can convert changes in temperature and strain into electrical signal changes, thus leading to multifunctional sensing performance. Based on these superior properties, a flexible e‐skin sensor is prepared, demonstrating its great potential in the wearable field and physiological signal detection. A new solvent‐free polymer conductive gel is obtained by combining flexible sulfonate‐containing poly(thioctic acid) polymer chains and rigid conductive polyaniline rods. The conductive gel shows good flexibility, puncture‐resistance, notch‐insensitivity, and fast self‐healing ability. Moreover, this conductive gel can convert changes in temperature and strain into electrical signal changes, and thus can be used for multifunctional electronic skin.